1999
DOI: 10.1002/(sici)1097-0231(19991215)13:23<2352::aid-rcm798>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray-assisted modification of proteins: a radical probe of protein structure

Abstract: A new approach is described to probe the structure of proteins through their reactivity with oxygen-containing radicals. Radical-induced oxidative modification of proteins is achieved within an electrospray ion source using oxygen as a reactive nebulizer gas at high needle voltages. This method facilitates the rapid oxidation of proteins as the molecules emerge from the electrospray needle tip. Electrospray mass spectra of both ubiquitin and lysozyme reveal that over 50% of the protein can be modified under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
161
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 117 publications
(171 citation statements)
references
References 41 publications
10
161
0
Order By: Relevance
“…Although not investigated in this study, another way of suppressing discharge could be the elimination of electrons produced during discharge by flushing the space around the spray tip with an electron scavenging gas such as SF 6 or CO 2 , or by the addition of a halogenated solvent to the liquid stream [20]. The converse approach of swamping the effect by using O 2 sheath gas (as in "radical probe MS" [6][7][8][9][10]) may complicate interpretation of H/D exchange data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not investigated in this study, another way of suppressing discharge could be the elimination of electrons produced during discharge by flushing the space around the spray tip with an electron scavenging gas such as SF 6 or CO 2 , or by the addition of a halogenated solvent to the liquid stream [20]. The converse approach of swamping the effect by using O 2 sheath gas (as in "radical probe MS" [6][7][8][9][10]) may complicate interpretation of H/D exchange data.…”
Section: Discussionmentioning
confidence: 99%
“…The converse approach of swamping the effect by using O 2 sheath gas (as in "radical probe MS" [6][7][8][9][10]) may complicate interpretation of H/D exchange data. Electron micrographs of emitter A and mass spectra acquired with it in the triaxial mode after 300 h use: (a) before polishing; (b) after polishing.…”
Section: Discussionmentioning
confidence: 99%
“…To explore further the interaction between this im-portant protein and the peptide melittin, we have applied an approach developed over a number of years to probe protein structure and interactions using oxygen-based radicals [21][22][23][24][25][26][27][28]. Briefly, proteins or their complexes are treated with a high flux of radicals on millisecond timescales that results in the limited (less than a few percent) oxidation of individual amino acid side chains.…”
mentioning
confidence: 99%
“…Briefly, proteins or their complexes are treated with a high flux of radicals on millisecond timescales that results in the limited (less than a few percent) oxidation of individual amino acid side chains. It has been found that where the reaction timescales are short (less than 10 -30 ms), the extent of oxidation at reactive amino acid residue side chains is highly influenced by the accessibility of these sites to the bulk solvent [21][22][23][24][25][26][27][28]. This would not be the case were the structure of the protein or complex to be perturbed.…”
mentioning
confidence: 99%
See 1 more Smart Citation